Characterization of morphological, micromorphological, anatomical structures and matK gene-based identification of aromatic litsea (Litsea cubeba) - ISMI NUR AINI; WISANTI WISANTI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Aini IN, Wisanti. 2023. Characterization of morphological, micromorphological, anatomical structures and matK gene-based identification of aromatic litsea (Litsea cubeba). Biodiversitas 24: 4557-4567. Aromatic litsea or krangean (Litsea cubeba (Lour.) Persoon) has potential as a drug. L. cubeba's status based on the IUCN red list is the least concern. This research aimed to (i) characterize morphology, micromorphology, and anatomy; (ii) indetify L. cubeba species based on DNA barcodes. The research samples were collected in the Mt. Anjasmoro, East Java, Indonesia at three different altitudes. Data in the form of various characters were analyzed using the one-way ANOVA method to determine the significance of the difference. The statistical test analysis of the quantitative character of L. cubeba showed a significant difference between heights (? = 0.05). The results showed that the characterization of L. cubeba includes (i) morphology: structure of lenticels, color, and substance that coats the lower surface of leaves, type of flower, fruit taste, and aroma; (ii) micromorphology: glands lining the abaxial surface of the lamina, trichomes on both surfaces of the lamina, structure of abaxial epidermal cells, the shape of pollen, shape and distribution of exin (iii) anatomy: cuticle thickness, epidermal cell shape, and presence of secretory cells in the lamina. The molecular identification in the form of L. cubeba barcode DNA based on the matK gene marker matched the Litsea cubeba sequence in NCBI (AB259073.1).